Evolution of Coronal Bright Points in Coronal Holes and a possible source of Solar Wind - Sattarov, I.; Karachik, N.V. (Известия Крымской астрофизической обсерватории, 2009)
On EIT and MDI data for 2007 coronal bright points (CBP) and magnetic bipoles (BP) output of coronal hole are studied. CBP and BP identification method developed by authors is used. Temporal variations of CBPs and BPs flux maximums are found, they took place before a fast solar wind maximum. On the base of similarity of longitudinal distribution frequency of coronal mass ejection and velocity of fast solar wind it is supposed that fast forced CBPs are source of fast solar wind.